Misleading advertising between the development of phenomenon and the deficiency of Algerian public rules. - Laassami, Ramzi Badreddine; Kahoul, Oualid (Journal of Human Sciences, 2021)
The deception has swept the commercial sphere of publicity in algeria , as it is now widely spread because of the evolution of its traditional and modern metohds, the economic agents use fraudulent methods to promote their products  and services in order to bring a high number of consumers by influencing their freedom of choice in pursuit of profits.This terrible expansion of the phenomenon is matched by legislative deficiency and the absence of a specific regulation in this vital area, as well as the inflexibility of general rules in the Civil and Penal Code of Algerian legislation to keep pace with the development of this scope and to provide the greatest protection to consumers as the vulnerable group in this economic process, as they are being affected by the damage.